EFEK TINGKAT KEBISINGAN PADA MASALAH PENDENGARAN PADA PEKERJA - Ella Anastasya Sinambela; Rahayu Mardikaningsih (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
Technological advances require the industry to use high-tech machines so that the company's productivity level increases. Technological machines make it easier for employees to work and can produce a better quantity of production compared to conventional machines. However, the existence of this machine has a negative impact on employees. This high-tech machine causes noise at the job site. The noise level that occurs causes health problems for employees, especially hearing health problems. This study is to determine the level of noise on hearing loss in workers. The population in this study were employees of an industry engaged in the manufacture of footwear products in Sidoarjo, East Java. This quantitative study uses the chi square test, 95% confidence level. The results of observations, there are 35 respondents (63.6%) have hearing loss and 20 respondents (36.4%) do not have hearing loss. The study also shows 38 respondents (69.1%) experience high noise levels in their workplace while 17 respondents (30.9%) experience low noise levels. The statistical test of the chi square test (X2) shows that noise intensity has an impact on the hearing of impaired workers. This is evidenced by the p value 0.000 which is lower than 0.05.